Analisis Kestabilan Penyebaran Penyakit Kolera Menggunakan Model SEIRS dengan Vaksinasi dan Faktor Treatment - Syafruddin Side; Sukarna; Gita Tri Asfarina (Journal of Mathematics, Computations and Statistics, 2018)
In this study, the rate of vaccination and treatment than to see the effects on the spread of the disease. In this case, obtained the minimum vaccination and treatment level of the minimum needed for the disease can disappear from the population. For vaccination rates and treatment level above the minimum vaccination and minimum treatment, the greater the rate of vaccination and treatment levels cause the proportion of Susceptible individuals getting smaller, meaning that people with cholera gradually diminishing and the disease will disappear from the population and there is no endemic.